Investigating the impact of stakeholder management on the implementation of a public access project: The case of Smart Cape - W. Chigona; D. Roode; N. Nazeer; B. Pinnock (South African Journal of Business Management, 2010)
This paper reports on a study that uses the Stakeholder Management Theory to analyse the implementation of a pilot phase of public access project, the Smart Cape Access Initiative, a Cape Town City Council e-government initiative. Data for the study was gathered through in-depth interviews with individuals who were involved, influenced and were affected by the implementation of the pilot project. The study identified the major stakeholders of the project and assessed their importance and influence on the project. Numerous interactions between the stakeholders were identified. It was further noted that no formal stakeholder management was undertaken at the identification and planning stages of the project lifecycle. In addition, results showed that there were missed opportunities for appropriate stakeholder management throughout the project. This study offers insights into agencies involved in planning and running public access projects.
Keywords: 650